Quality monitoring in laser welding of rectangular copper wires for traction drives using a laser Doppler vibrometer - Baader, Marcel; Raffin, Tim; Giesbert, Fabian; Franke, Jörg (Proceedings Volume 13436, Nondestructive Characterization and Monitoring of Advanced Materials, Aerospace, Civil Infrastructure, and Transportation XIX, 2025)
The electrification of vehicles poses significant challenges to automotive manufacturers, particularly in the production of electric traction drives. Winding concepts such as Hairpin, I-pin, or X-pin technology are increasingly relying on the use of rectangular copper wires instead of round wires for stator windings. Here, a large number of connection points between individual winding sections have to be realized by laser welding and are crucial for overall functionality and product quality. To ensure the quality of each of these joints, process monitoring with in-process capable sensors is increasingly being pursued. This paper focuses on whether the quality of the welds can be monitored using a laser Doppler vibrometer (LDV). Therefore, the vibration behavior of the welding process and the molten material is analyzed and correlations between the vibrations and features of welding quality, such as pore formation or cross-section area (CSA), are investigated. For this purpose, the study is based on a design of experiments, which provides welds of varying quality. While welding, the vibration behavior of the melt is monitored with the LDV. The LDV records the movements of the copper surface (solid as well as liquid) as relevant process parameters. The time-series characteristics of the LDV signals for displacement and velocity are analyzed to determine whether they correlate with the welding quality. The findings demonstrate that LDVs can serve as an effective tool for monitoring the welding quality of rectangular copper wire